Peran Penyuluh Pertanian dalam Pembuatan Pupuk Organik melalui Budidaya Maggot di Desa Sukamakmur Kecamatan Ajung Kabupaten Jember - Mohammad Wiki Candra; Sofia Sofia; Diah Puspaningrum; Lenny Luthfiyah (AGRITEXTS: Journal of Agricultural Extension, 2024)
This research aims to determine the role of agricultural extensionist in making organic fertilizer through maggot cultivation in Sukamakmur Village, Ajung Sub-district, Jember Regency. This research uses qualitative descriptive approach. Data collection uses observation, in-depth interviews, and documentation. Data analysis uses Miles and Huberman model. The research results show that role of agricultural extensionist in making organic fertilizer through maggot cultivation is divided into three processes, namely planning, management and results of maggot cultivation. In planning, extension workers carry out role of analysts in identifying environment through site surveys, checking tools, materials and feed. Extension agents as facilitators help provide tools and materials, capital and look for market opportunities. Extension agents as organizers carry out coordination, communication and evaluation. As an extension dynamist, mobilizes members of Tirto Bakti II farmer group to actively participate in comparative studies and bazaars. The role of motivator is carried out by motivating in verbal communication and plot demonstration. Extensionist as initiator provides suggestions in making derivative products such as fish feed, creating new packaging and labels. In management, extensionist as teachers/mentors carry out socialization and training activities. As a liaison, extensionist helping in preparing proposals of request assistance and facilities to the government. As advisors, extensionist advise on maintaining sustainability of maggot cultivation so that it continues to operate and increases the targets to be achieved. In the results of maggot cultivation, as agents of change, extensionist influence communities’ mindset to utilize waste through maggot cultivation and meet fertilizer needs with organic fertilizers.